2014
DOI: 10.11120/ened.2014.00024
|View full text |Cite
|
Sign up to set email alerts
|

New Civil Engineer: Introducing Undergraduate Civil Engineers to Construction Technology

Abstract: Undergraduate (UG) civil engineering students should graduate from university with knowledge that links their computational competence in structural engineering and mechanics to construction technology principles, processes and practice. However, there appears to be a paucity of evidence to suggest that UG civil engineering students receive sufficient instruction in construction technology throughout their degree studies. This paper presents evidence from a study employing the weekly New Civil Engineer (NCE) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This confirms Trevelyan (2014) who argued that you do not have to be working in an engineering job to develop leadership and team working abilities. Murray et al, (2019) found similar views of civil engineering students employed in non-engineering summer jobs, with self-reported improvements in their communication and teamworking skills. Of note, Evans & Yusof (2020) have argued for students' who secure part time work to consider how this can help demonstrate the skills required in their future professional careers, and, for employers of students to consider how they can assist them in skills development rather than only monetary benefits.…”
Section: Extra-curricular Activitiesmentioning
confidence: 56%
“…This confirms Trevelyan (2014) who argued that you do not have to be working in an engineering job to develop leadership and team working abilities. Murray et al, (2019) found similar views of civil engineering students employed in non-engineering summer jobs, with self-reported improvements in their communication and teamworking skills. Of note, Evans & Yusof (2020) have argued for students' who secure part time work to consider how this can help demonstrate the skills required in their future professional careers, and, for employers of students to consider how they can assist them in skills development rather than only monetary benefits.…”
Section: Extra-curricular Activitiesmentioning
confidence: 56%
“…Whilst this truism is apt for many professional disciplines, for undergraduates in civil engineering this statement of fact resonates more profoundly. Despite recent initiatives to introduce civil engineering at 'grassroots' level (see ICE, 2017), the pathway to becoming a professional civil engineer is not addressed prior to university enrolment (Murray and Tennant, 2014) in any substantive manner.…”
Section: Becoming a Professional Civil Engineermentioning
confidence: 99%
“…Anecdotal evidence indicates that the majority of first year civil engineering undergraduates enrolling at university are both technically and professionally naïve (Murray and Tennant, 2014). Given this dual academic and professional naivety, a meaningful civil engineering curriculum ought to address and give undergraduates access to both academic and situated cognition.…”
Section: Becoming a Professional Civil Engineermentioning
confidence: 99%
“…Thus, new approaches have been recommended in various engineering disciplines; e.g. Mechanical Engineering (Fernandes Teixeira et al, 2007), Electrical Engineering (Wilson et al, 2011), Civil Engineering (Murray and Tennant, 2014) and Chemical Engineering (Glassey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%